PENAFSIRAN AYAT ANTROPOMORFIS DALAM SAFWAT AL-TAFASIR - Solehodin; Faruq, Umar (Jurnal Al I'jaz, 2024)
Saudi Arabia is constitutionally a monarchy. Saudi Arabia is ruled by a king from the Saud family (Ali Saud). In order to sustain political power, the kingdom joined hands with the Wahabi school, which rejects heresy, shirk, khurafat and superstition. Through this dual power, the development of Islamic science in Saudi Arabia experienced a significant change. The works that were born were influenced by Wahabi ideological politics to become the grand madzhab there. In the author's search, there is also a work that was born in Saudi Arabia with the Sunni school of thought, namely Safwat al-Tafasir. This article is organized to see that the phenomenon is different from the supposed facts. It focuses on the anthropomorphic of Al-Qur'an Surah al-Baqarah [2]: 255, Al-Qur'an Surah Taha [20]: 5, Al-Qur'an Surah Sad [38]: 75 and Al-Qur'an Surah al-Qiyamah [75]: 23. This article is a qualitative research compiled with descriptive-analytical method. The data is collected through library research. In the end, the research found a bright spot about the methodical aspects of Muhammad ‘Ali al-Sabunii's work. The method of tafsir is tafsir tahlili (analysis), using sources of history and ratios that are patterned al-adab al-ijtima'i (social society). From the aspect of theological madhhab, Muhammad ‘Ali al-Sabuni can be said to be a Sunni group. This assumption is based on the author's discovery of anthropomorphic.